ArcCRUST: Arctic crustal thickness from 3D gravity inversion, links to files in NetCDF format - Lebedeva-Ivanova, Nina; Gaina, Carmen; Minakov, Alexander; Kashubin, Sergei (Supplement to: Lebedeva-Ivanova, N et al. (2019): ArcCRUST: Arctic Crustal Thickness From 3-D Gravity Inversion. Geochemistry, Geophysics, Geosystems, 20(7), 3225-3247, https://doi.org/10.1029/2018GC008098, 2019)
The ArcCRUST model consists of crustal thickness and estimated crustal thinning factors grids for the High Arctic and Circum-Arctic regions (north of 67°N). This model is derived by using 3D forward and inverse gravity modelling. Updated sedimentary thickness grid, an oceanic lithosphere age model together with inferred microcontinent rifting ages, variable crystalline crust and sediment densities, and dynamic topography models constrain this inversion. We use published high-quality 2D seismic crustal-scale models to create a database of Depths to Seismic Moho (DSM) profiles. To check the quality of the ArcCRUST model, we have performed a statistical analysis of misfits between the ArcCRUST Moho depths and DSM values. Systematic analysis of the misfits within the Arctic sedimentary basins provides information about tectonic processes unaccounted by the assumed model of pure-shear lithospheric extension. In particular, our model implies a less-dense and/or thin mantle lithosphere underneath microcontinents in the deep Arctic Ocean where the ArcCRUST depth to Moho values exceed the depth to seismic Moho. A systematically larger gravity-derived crustal thickness (ca. 3 km) under the western and northern Greenland Sea points to a hotter upper mantle implied by the seismic tomography models in the North Atlantic.
Keywords: Arctic; crutsal thickness; Moho; oceanic lithosphere; sediment thickness